Medical Bacteriology A Practical Approach - Hawkey, Peter M;Ed. Lewis, D. A;Ed (Practical Approach Series, 1989)
This book is a concise guide to the range of diagnostic procedures performed in laboratories' processing and reporting on clinical bacteriology specimens. Methods are described as they would be encountered in the laboratory.